2010
DOI: 10.1111/j.1600-0463.2010.02641.x
|View full text |Cite
|
Sign up to set email alerts
|

Type-specific human papillomavirus detection in cervical smears in Romania

Abstract: To study type 1 diabetes (T1D), excellent animal models exist, both spontaneously diabetic and virus-induced. Based on knowledge from these, this review focuses on the environmental factors leading to T1D, concentrated into four areas which are: (1) The thymus-dependent immune system: T1D is a T cell driven disease and the beta cells are destroyed in an inflammatory insulitis process. Autoimmunity is breakdown of self-tolerance and the balance between regulator T cells and aggressive effector T cells is distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 179 publications
2
10
1
Order By: Relevance
“…The proportion of Eastern European migrants with normal cytology and with HPV infection (56.1%) is much higher than that reported in Russian Federation (29.1%) (15) or in the former Soviet Union states (27.4%) (16). Recent studies, however, conducted in Romania and in Estonia showed that HPV rates among women negative for intra-epithelial lesions and malignancy were 43.5% and 36.8%, respectively (29,30). In both countries, the high prevalence of HPV infection in the general population correlates with a very high incidence of invasive cervical cancer (31 new cases ⁄ 100 000 women in Romania and 21.5 new cases ⁄ 100 000 women in Estonia) (31).…”
Section: Discussionmentioning
confidence: 74%
“…The proportion of Eastern European migrants with normal cytology and with HPV infection (56.1%) is much higher than that reported in Russian Federation (29.1%) (15) or in the former Soviet Union states (27.4%) (16). Recent studies, however, conducted in Romania and in Estonia showed that HPV rates among women negative for intra-epithelial lesions and malignancy were 43.5% and 36.8%, respectively (29,30). In both countries, the high prevalence of HPV infection in the general population correlates with a very high incidence of invasive cervical cancer (31 new cases ⁄ 100 000 women in Romania and 21.5 new cases ⁄ 100 000 women in Estonia) (31).…”
Section: Discussionmentioning
confidence: 74%
“…The high prevalence of HSIL in the present study draws attention to the fact that the prevalence of high-risk HPV subtypes is probably much higher in Romania than in other countries [22][23][24][25][26], although these data are from only small study samples. Another explanation might be the unequal distribution of cases by age group in the present study (Table 4): 38.7% of abnormal samples were in the age group 30-39 years; 20.0% in the age group 40-49 years (the incidence of HSIL peaked at approximately 40 years of age); 17.8% in the age group 25-29 years; and 14.0% in the age group 24 years and younger (the incidence of LSIL peaked a decade earlier than that of HSIL).…”
Section: Discussionmentioning
confidence: 92%
“…In order to study the possible role of TLR4 in diabetes development, we generated a TLR4-deficient strain of the NOD mouse, the currently best characterized model of human type 1 diabetes [27] and analysed diabetes progression by in vivo and in vitro approaches.…”
Section: Introductionmentioning
confidence: 99%